Structural Adjustments and Deforestation in Nicaragua - Solveig Glomsrød; Maria Dolores Monge A.; Haakon Vennemo (Statistics Norway, Research Department, 1997)
This paper investigates the impact of structural adjustment policies on deforestation taking place when the agricultural frontier advances into forest reserves in Nicaragua. A computable general equilibrium model incorporating deforestation by squatters is used for policy simulations. The opportunity cost of migrating to the frontier does not simply depend on wage income opportunity, but also on market prices of basic grain which determine the capacity to consume beyond subsistence food level within a certain real wage. Reducing public expenditures both conserve forests and enhance economic growth, while showing positive distributional effects. On the other hand, a strong conservation trend following a sales tax increase is driven by increasing poverty in rural areas. Noticeably, there are policies which initially intensify deforestation, but turn out to ease the pressure on forests over time. Rapid economic growth does not ensure less pressure on forest reserves.
Keywords: C68; O54; Q23; R23; 330; Deforestation; structural adjustment; general equilibrium model; Nicaragua